Kerentanan Dan Ragam Ancaman Keamanan Di Provinsi Lampung - Gita Karisma; Iwan Sulistyo; Indra Jaya Wiranata (Terekam Jejak Publisher, 2024)
This research explains the various vulnerabilities and security threats faced by Lampung Province. This study is based on the fact that there has been an increase in types of threats at the global level from year to year, at least in the last three years. At the nation-state level, Indonesia is also aware of the increasingly complex variety of threats. This can be seen from the explanation in the Indonesian Defense White Papers which had been published in 2003, 2008, and 2015. One of the critical subnational entities to study is Lampung. The analytical frameworks used are the concepts of city security and vulnerability. Data were collected through a literature review with data sources from a number of official online pages, namely BPS Lampung Province, UNDP, WALHI, and others. This project reveals that there were threats and vulnerabilities carried by Lampung Province, including environmental, economic, political and social security.